2014
DOI: 10.1111/febs.12823
|View full text |Cite
|
Sign up to set email alerts
|

Defining critical residues for substrate binding to 1‐deoxy‐d‐xylulose 5‐phosphate synthase – active site substitutions stabilize the predecarboxylation intermediate C2α‐lactylthiamin diphosphate

Abstract: 1-Deoxy-d-xylulose 5-phosphate (DXP) synthase catalyzes formation of DXP from pyruvate and d-glyceraldehyde 3-phosphate (d-GAP) in a thiamin diphosphate (ThDP)-dependent manner, and is the first step in the essential pathway to isoprenoids in human pathogens. Understanding the mechanism of this unique enzyme is critical for developing new anti-infective agents that selectively target isoprenoid biosynthesis. The present study uses mutagenesis and a combination of protein fluorescence, circular dichroism and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 30 publications
4
85
0
Order By: Relevance
“…Earlier, it was reported that Arg478 is important for GAP binding and its recognition, but not crucial for catalysis through LThDP formation. 9 Again, the characteristic negative CD band at 320 nm was not apparent on MeOThDP binding (Figure S7). Upon titration with donor substrate pyruvate, the positive CD band at 313 nm assigned earlier to LThDP was also evident for the Arg478Ala DXPS complexed with ThDP, but not with MeOThDP (Figure S7).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier, it was reported that Arg478 is important for GAP binding and its recognition, but not crucial for catalysis through LThDP formation. 9 Again, the characteristic negative CD band at 320 nm was not apparent on MeOThDP binding (Figure S7). Upon titration with donor substrate pyruvate, the positive CD band at 313 nm assigned earlier to LThDP was also evident for the Arg478Ala DXPS complexed with ThDP, but not with MeOThDP (Figure S7).…”
Section: Resultsmentioning
confidence: 97%
“…9 The assay mixture (2.4 mL) contained 50 mM KH 2 PO 4 , 50 mM Tris-HCl (pH 8.0), 0.1 M NaCl, 0.10 mM ThDP (0.10 mM MeOThDP), 2.0 mM MgCl 2 , 1.0 mM pyruvate, 1.0 mM DTT, 1 mM GAP, and 1% glycerol. The reaction was started by addition of 0.02 mg of DXPS, and the spectrum was recorded for 400 s at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…CD experiments, complemented with the TH method to assist the CD assignments, revealed that formation of LThDP is rate-limiting overall in the sequence of reactions carried out by DXPS [63,64]. However, LThDP is remarkably stable on the enzyme until the acceptor D-GAP is added.…”
Section: The Covalent Substrate-mentioning
confidence: 99%
“…Structural studies of DXP synthase indicate the enzyme possesses unique domain architecture 17 and an unusually large active site volume; 18 these observations are consistent with mechanistic studies offering support for ternary complex formation in DXP synthase catalysis. 1922 Our mechanistic studies suggest GAP serves two distinct roles in DXP formation, as a trigger for lactyl thiamin diphosphate (LThDP) decarboxylation and as an acceptor substrate during carboligation. 21,22 As new insights emerge about the distinctive characteristics of DXP synthase, so will new opportunities for the development of selective inhibitors.…”
mentioning
confidence: 99%